Topographical and morphological aspects of spray coated organic photovoltaics - Hoth, Claudia N.; Steim, Roland; Schilinsky, Pavel; Choulis, Stelios A.; Tedde, Sandro F.; Hayden, Oliver; Brabec, Christoph J. (My University, 2009)
Herein we discuss the topographical and nanomorphological aspects of spray deposited organic photovoltaics. We show that the solvent properties have a massive impact on the topography, but less on the nanomorphology formation of composites based on the electron donor poly(3-hexylthiophene) (P3HT) and the electron acceptor [6,6]-phenyl C61 butyric acid methyl ester (PCBM). An adapted solvent mixture consisting of ortho-dichlorobenzene (oDCB) and 1,3,5-trimethylbenzene (mesitylene) allows us to demonstrate spray coated organic photovoltaic devices with 3.1% power conversion efficiency (PCE). Moreover, we show that spray coating is a feasible technology to deposit all solution processable layers of organic solar cells, including the hole transporting layer poly(3,4-ethylene dioxythiophene) doped with polystyrene sulphonic acid (PEDOT:PSS) as well and demonstrate fully spray coated devices with 2.7% PCE.
Keywords: Spray coating; Photovoltaics; Solar cells; Polymers; Fullerenes; P3HT